2.72. Sprawdź, czy liczba b jest odwrotnością liczby a: a) a = sqrt(7) – sqrt(6) b = sqrt(7) + sqrt(6) d) a = 2sqrt(3) + sqrt(11) b = 2sqrt(3) – sqrt(11) b) a = sqrt(3) – 2 d) a = sqrt(5) – sqrt(6) b = – sqrt(5) – sqrt(6) b = sqrt(2) – sqrt(3) e) a = sqrt(6) – 2sqrt(2) b = sqrt(6) + 2sqrt(2) f) a = – sqrt(2) – sqrt(3)

2.72. Sprawdź, czy liczba b jest odwrotnością liczby a: a) a = sqrt(7) – sqrt(6) b = sqrt(7) + sqrt(6) d) a = 2sqrt(3) + sqrt(11) b = 2sqrt(3) – sqrt(11) b) a = sqrt(3) – 2 d) a = sqrt(5) – sqrt(6) b = – sqrt(5) – sqrt(6) b = sqrt(2) – sqrt(3) e) a = sqrt(6) – 2sqrt(2) b = sqrt(6) + 2sqrt(2) f) a = – sqrt(2) – sqrt(3)